CARDIOTOXICITY AND METHODS OF ITS DIAGNOSIS IN HEMATOLOGY PATIENTS (REVIEW) - T. P. Kuzmina; I. L. Davydkin; O. V. Tereshina; O. E. Danilova; A. S. Shpigel; T. Sh. Betaneli; K. V. Naumova; N. S. Popelnyuk (Сибирский научный медицинский журнал, 2019)
The article is devoted to the modern concept of cardiotoxicity, induced chemotherapy in patients with hematological pathology and methods of its diagnosis. The study of cardiotoxicity is one of the current trends in oncology and oncohematology, as the side effects of chemotherapy drugs on the cardiovascular system affect the quality and life expectancy of patients, regardless of the prognosis associated with oncohematological disease. While modern strategies for the treatment of oncohematological diseases make it possible to achieve stable remissions and increase the duration and quality of life of patients, such successes can be offset by an increase in mortality in this group of patients due to the development of side effects of chemotherapy in relation to the cardiovascular system. In the review problems and prospects of cardiotoxicity diagnosis in patients with hematological diseases on the background of chemotherapy are presented at modern level of medical science development. The use of such methods as three-dimensional echocardiography, echocardiography with determination of global longitudinal myocardial deformation, stress echocardiography with determination of contractile reserve, determination of troponin and natriuretic peptide levels for diagnosis of cardiotoxicity makes it possible to detect manifestations of cardiotoxicity at an earlier stage and thus will reduce mortality in patients with oncohematological profile receiving chemotherapy for non-hematological reasons.